Influence of landscape context on patterns of occupancy, abundance, and gene flow among collared lizards in the Flint Hills of Kansas - Blevins, Emilie (Kansas State University, 2010)
Organisms exist within complex landscapes, and landscape features may influence multiple aspects of a species’ distribution within the landscape, including patch occupancy, abundance within patches, and population genetic diversity at a local or regional scale. We took two approaches to identify the relative importance of landscape context for populations of the Eastern Collared Lizard (Crotaphytus collaris collaris) in the northern Flint Hills of Kansas. First, we conducted surveys at limestone outcrops in experimental watersheds managed under different burning and grazing practices. Habitat occupancy and lizard abundance were estimated by constructing models that incorporated aspects of the environment at multiple scales. Both abundance and occupancy were higher on rock ledges that had more crevices, greater complexity in vegetation, covered a larger area, and were more prominent than available habitat. Abundance and occupancy were also higher in watersheds that were burned frequently (1–2 year intervals), but grazing only had a significant effect in less frequently burned (four–year burn interval) watersheds. Our second approach was to measure genetic diversity and population genetic differentiation and relate these measures to differences in landscape context. We sampled collared lizard DNA at four locations (sample sites < 45 km apart) and analyzed trends in 10 polymorphic microsatellite loci. We found evidence for low genetic variability and moderate population differentiation among our sample sites relative to estimates reported in the literature at the core of the species’ range. Differences in migration rates and ancestry among sampling locations also appear to correspond to differences in landscape resistance based on land cover and rock availability. Thus, it appears that habitat management may influence the suitability of habitat patches at the local scale, and that differences in land cover and rock availability may influence the connectivity of populations at the landscape scale.
Keywords: Crotaphytus collaris; landscape context; Biology, Ecology (0329)